Comparative Study Of Current Control Strategy For DC Motors - Lukar Herlino, Adeline; Jidin, Auzani; Che Wan Mohd Zalani, Che Wan Mohd Faizal; Sanusi, Syamim; Jopri, Mohd Hatta; Manap, Mustafa (2013)
A brushed DC motorist well-known to provide simple control and superior torque dynamic performance. This is mainly due to the fact that the electromagnetic torque can be directly controlled by regulating the armature current using full bridge DC-DC converter. Note that the developed torque is proportionally to the armature current and the use of full bridge converter permits the motor performs into 4-quadrant operation. This paper will present a comparative study of current/torque performances for three different current control strategies which are as follows; 1) hysteresis-based with bipolar switching technique, 2) carrier-based with bipolar switching technique and 3) carrier-based with unipolar switching technique. The comparison performances of the switching techniques will be analyzed through experimental results.